PENGARUH SERVICE EXCELLENT PETUGAS CHECK IN COUNTER TERHADAP KEPUASAN PENUMPANG PADA BANDAR UDARA KOMODO LABUAN BAJO - Ramadan, Teggar; Frisnawati, Elnia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The purpose of this study was to determine the effect of excellent check-in counter service on passenger satisfaction at Komodo Labuan Bajo Airport. To determine the magnitude of the influence of excellent check-in counter service on passenger satisfaction at Komodo Labuan Bajo Airport. This study uses a quantitative method. The population is passengers at Komodo Labuan Bajo Airport with a sample of 100 employees. Data collection techniques using questionnaires. Data analysis using multiple linear regression analysis. Hypothesis testing using t-test, F-test, coefficient of determination. The results showed that there was a significant effect of excellent check-in counter service on passenger satisfaction at Komodo Labuan Bajo Airport. This is evidenced by the t-count value of 14.453 with a significance value of 0.000 smaller than 0.05 (0.000 <0.05), and the regression coefficient has a positive value of 0.880. The results of the magnitude of the influence show that the adjusted R value (coefficient of determination) is 0.681. This means that 68.1% of the passenger satisfaction variable is influenced by the independent variable, namely the excellent service of the check-in counter officer (X). While the remaining 31.9% of the passenger satisfaction variables are influenced by other variables that are not discussed in this study.